Neonatal sepsis following prolonged rupture of membranes in a tertiary care hospital in Karachi, Pakistan - Muhammad Matloob Alam; Ali Faisal Saleem; Abdul Sattar Shaikh; Owais Munir; Maqbool Qadir (Journal of Infection in Developing Countries)
Introduction: Prolonged rupture of membrane (PROM) is an important risk factor for early onset neonatal sepsis (EONS), which is associated with increased neonatal morbidity and mortality. We reported the incidence and associated risk factors of PROM for culture-proven EONS. Methodology:The medical records of all neonates born at Aga Khan University, Karachi over a period of five years (2007-2011) with PROM (> 18 hours) were reviewed. Data about maternal and neonatal risk factors for EONS was collected and adjusted logistic regression (AOR) analysis was applied. Results:Incidence of PROM in this neonatal birth cohort was 27/1,000 live births. A total of 17 (4%) cases with blood-culture proven bacterial sepsis were identified within 72 hours of birth. Klebsiella pneumonia (n = 5; 29%) and Pseudomonas aeruginosa (n = 4; 24%) were the commonest isolates followed by group B Streptococcus (n = 3; 18%) and Escherichia coli (n = 2; 12%). Maternal fever (p = <0.001; AOR, 36.6), chorioamnionitis (p < 0.001; AOR, 4.1), PROM > 48 hr. (p < 0.001; AOR, 8.2), neonatal prematurity < 34 weeks (p < 0.001; AOR, 4.1) and low birth weight < 1,500 grams (p 0.001; AOR, 9.8) along with neonatal thrombocytopenia and raised CRP were found to be independent risk factors associated with culture-proven EONS in PROM. Conclusions: Preventive measures should focus on recognition of these high-risk infants with prompt laboratory screening for sepsis and early institution of empirical antibiotic based on local data. Such approaches would be a safe and cost-effective strategy, especially in developing countries.